Acute anterior hypopyon uveitis after non-penetrating ocular trauma in a patient with ankylosing spondylitis and HLA-B27 positivity - Garza Garza, Lucas; Ramos-Davila, Eugenia; Ruiz-Lozano, Raul; Morales, Gustavo; Alvarez-Guzman, Carlos; Rodriguez-Garcia, Alejandro (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Acute anterior uveitis is the most common type of uveitis. Subsequent reactivation of acute anterior uveitis after the successful control of an initial episode has been linked to several risk factors. Less commonly, acute anterior uveitis reactivation has been associated with a traumatic stimulus. We present the case of a 55-year-old man with a 2-year history of neck and low-back pain and morning stiffness and a family history of rheumatoid arthritis. He presented to the outpatient clinic complaining of blurry vision in his left eye after a nonpenetrating trauma with a frosted glass splinter. A corneal leucoma corresponding to the trauma and an acute anterior uveitis with a hypopyon was found in his left eye. Further rheumatological evaluation yielded a diagnosis of HLA-B27 positive ankylosing spondylitis. The acute anterior uveitis resolved without complications with topical steroids and cycloplegics. The present case and others previously reported suggest that ocular trauma could be a trigger of AAU in predisposed patients. Furthermore, a systemic evaluation should be considered in patients with ocular inflammation out of proportion to a traumatic stimulus and who present systemic symptoms compatible with diseases known to cause ocular inflammation.